2013
DOI: 10.3748/wjg.v19.i10.1632
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in patients with obscure gastrointestinal bleeding after negative capsule endoscopy

Abstract: Patients with OGIB and negative CE have a potential risk of rebleeding. Therefore, close observation is required and alternative modalities should be considered in suspicious cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 28 publications
8
36
1
1
Order By: Relevance
“…Remarkably, the majority of re-bleeding episodes (81.3%) occurred within the first 2 years after VCE examination, while the cumulative risk of re-bleeding raised from 12.9% at 1, to 25.6% at 3 and to 31.5% at 5 years, respectively (31); this finding being verified by other authors (29). In keeping with the findings of previous reports (25,32), the median time until first rebleeding event was 15 months, underlying the value of patient monitoring for at least the first 2 years post negative VCE exam and perhaps later on, as the interquartile range for the time lag to re-bleeding was between 2 and 33 months (31).…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationsupporting
confidence: 82%
See 1 more Smart Citation
“…Remarkably, the majority of re-bleeding episodes (81.3%) occurred within the first 2 years after VCE examination, while the cumulative risk of re-bleeding raised from 12.9% at 1, to 25.6% at 3 and to 31.5% at 5 years, respectively (31); this finding being verified by other authors (29). In keeping with the findings of previous reports (25,32), the median time until first rebleeding event was 15 months, underlying the value of patient monitoring for at least the first 2 years post negative VCE exam and perhaps later on, as the interquartile range for the time lag to re-bleeding was between 2 and 33 months (31).…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationsupporting
confidence: 82%
“…Studies reporting very low re-bleeding rates had relative short follow-up (17,19,21,36,40,41). Contrariwise, Korean studies enrolled relatively more subjects with longer follow-up, exceeding 2 years (32,34,35,37). This possibly allowed Park et al (34) to display a re-bleeding rate of 35.7% during the 32 months follow-up, while Koh et al (32) showed that more than half of the patients suffered bleeding recurrence more than 1 year after the initial episode with the maximum time to re-bleeding being 24 months post-procedurally.…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationmentioning
confidence: 99%
“…In addition, 50-66% of patients have been reported to remain transfusion free without recurrent bleed at follow-up, aft er undergoing VCE-directed interventions ( 43,45 ). Th e rebleeding rate ranges from 6 to 27% in patients who have had a negative capsule study (46)(47)(48).…”
Section: Endoscopic Visualization Of the Small Intestinementioning
confidence: 96%
“…La recomendación actual es utilizar polietilenglicol (PEG) diluido en 2 litros de agua, bien sea como monoterapia o en combinación con simeticona, para garantizar una mejor calidad en la preparación y, por ende, una mayor rendimiento diagnóstico (27). Luego de dos horas de haber iniciado el estudio, el paciente puede tomar líquidos y, pasadas cinco horas, alimentarse normalmente (28).…”
Section: Videocápsula Endoscópica (Vce)unclassified